Efficiency Analysis of Lloyd's Syndicates: A Comparison of DEA and SFA Approaches - Milton Nektarios; Panos Xenos; George Nektarios; Kostas Poulakis; Michalis Chouzouris (SPOUDAI - Journal of Economics and Business, 2015)
This paper evaluates the efficiency of the twenty-one largest Syndicates of Lloyd's of London. Members of Lloyd's of London are grouped into Syndicates in order to undertake insurance liabilities. In this study, the Syndicate is regarded as the counterpart of an insurance company in a regular insurance market. The analysis covers a period of eight years between 2004 and 2011. Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) are used to estimate the efficiency of the Syndicates, and comparisons are made for the consistency of the two methods. The main findings indicate, firstly, that the average annual efficiency estimates for all Syndicates are plausible and they follow three-year cycles. Secondly, the less efficient syndicates may reduce inputs by almost one-third and still produce the same output, provided that they adopt the "best practices" of the most efficient Syndicates.
Keywords: G22; D24; D22; 330; Insurance; Lloyd's; efficiency; DEA; SFA